The carp in the bathtub - Cohen, Barbara; Halpern, Joan (Rockville, MD : Kar-Ben Copies, 1987)
Two children try to rescue the carp their mother plans to make into gefilte fish for the Seder.
Keywords: Jews -- United States -- Fiction